2021
DOI: 10.31234/osf.io/n7e9p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability and Validity of the Mental Health Quotient (MHQ)

Abstract: Background: The MHQ is an assessment of mental health and wellbeing that comprehensively covers symptoms across 10 major psychiatric disorders as defined by the DSM-5, in addition to constructs defined by RDoC and positive dimensions of mental function using a novel life-impact scale. An overall measure of mental wellbeing, the Mental Health Quotient or MHQ, is computed based on these elements using a nonlinear transformation of the scale followed by a rescaling. The MHQ has been deployed as part of the Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…While all demographic factors together were effective at predicting MHQ sign, young age (i.e., being 18-24 followed by 25-34) was disproportionately powerful as a predictor of negative mental health. This is supported by other evidence that shows overall mental health status is worse for each younger age group: data from the Mental Health Million Project has shown that in 2021, 44% of young adults (18-24 years) were mentally distressed or struggling compared to 7% among those aged 65 and above [72], while other studies also highlight the increase in mental health problems in teens [2] [3]. This is in sharp contrast to psychological wellbeing patterns observed prior to 2010 where young adults were typically at the higher end of wellbeing scales [86] [87].…”
Section: The Relative Impact Of Individual Determinantssupporting
confidence: 65%
See 1 more Smart Citation
“…While all demographic factors together were effective at predicting MHQ sign, young age (i.e., being 18-24 followed by 25-34) was disproportionately powerful as a predictor of negative mental health. This is supported by other evidence that shows overall mental health status is worse for each younger age group: data from the Mental Health Million Project has shown that in 2021, 44% of young adults (18-24 years) were mentally distressed or struggling compared to 7% among those aged 65 and above [72], while other studies also highlight the increase in mental health problems in teens [2] [3]. This is in sharp contrast to psychological wellbeing patterns observed prior to 2010 where young adults were typically at the higher end of wellbeing scales [86] [87].…”
Section: The Relative Impact Of Individual Determinantssupporting
confidence: 65%
“…This includes demonstration that, in the aggregate, average number of clinical symptoms and clinical diagnoses increase systematically as MHQ scores decrease, and that MHQ scores are linearly related to work productivity, including absenteeism and presenteeism [69]. Population MHQ scores also align with well-established trends relating to age, employment, education, physical exercise, sleep and social engagement, as well as being generally higher in males than females [72].…”
Section: The Mental Health Quotient (Mhq)mentioning
confidence: 69%
“…The results of the Mental Health Million project, which is a survey on global mental wellbeing launched by Sapien Labs, revealed that in 2021, more than 50% of people with clinical mental health risks did not seek psychological help. It also stated that 25% of those not seeking help cited stigma as the leading cause ( 8 ).…”
Section: Introductionmentioning
confidence: 99%